Sourcing and engaging the crowd: Audience interaction and participation in online-only slow journalism platforms - Knaudt, Lena; Siebe, Renske; Harbers, Frank; Graham, Todd (AoIR Selected Papers of Internet Research, 2016)
The rise of web 2.0 has deeply affected journalism. While the horizontal architecture of the Internet can potentially extend and improve the public sphere, legacy news media seem reluctant to embrace the democratic potential of interactive new media. In comparison, online-only ‘slow journalism’ startups like De Correspondent and Krautreporter in respectively the Netherlands and Germany stress the benefits of audience participation.This paper examines to which extent these startups re-negotiate journalism practice in light of the increasingly participatory discourse of Internet culture. Our research seeks to illuminate three main questions: What is the nature of the debate amongst the audience of these outlets? How do journalists engage with the audience? How do journalists and the audience together negotiate journalism’s quality standards?Our research will be based on a quantitative content analysis and a textual analysis of all the comments on articles published in both outlets in April 2016. To measure the nature of journalists-audience interaction, each comment will be coded for the type of interaction (with the content, journalist, and/or participant), function (e.g. arguing, acknowledging/thanking, criticizing/defending journalism) and influence (e.g. receiving replies, changing the tone of debate).So far, few empirical studies have analyzed audiences-journalist exchanges in comment fields, and they often find little actual interaction. Due to the focus of slow journalism on a highly educated audience and their emphasis on the value audience participation, we expect our cases to show a significantly higher level of interaction and a considerable degree of democratic quality during discussions.